Bacillus Bloodstream Infections in a Tertiary Perinatal Centre: An 8-Year Study - Ting, Joseph Yuk; Wong, Samson Sai-yin; Chee, Yuet-yee; Wong, Kar-yin; Tsoi, Nelson Nai-shun; Lau, Allan S. Y. (American Journal of Perinatology, 2013)
Background Isolates of nonanthrax Bacillus species in clinical samples are frequently considered as contaminants. However, there were case reports describing Bacillus sepsis among infants, associated with high mortality and morbidity.Methods We performed a retrospective review of the clinical and epidemiological features of Bacillus bacteremia at our neonatal intensive care unit from January 2002 to December 2009.Results Bacillus bacteremia was considered to be clinically significant in 11 infants. The median gestational age was 30 weeks. All had either central catheters or peripherally inserted arterial lines in situ. The mean neutrophil and lymphocyte counts were 6.73 × 109/L (0.78 to 12.56 × 109/L) and 2.75 × 109/L (0.82 to 6.15 × 109/L), respectively. All 11 infants received intravenous vancomycin, with an average duration of 12.4 days. In general, the earlier the catheter was removed, the quicker the clearance of bacteremia was achieved. All infants survived and were discharged from the hospital.Conclusions The growth of Bacillus species in blood cultures cannot simply be regarded as a contaminant. Hematologic parameters are frequently unremarkable at the disease onset. Increased vigilance, early diagnosis, and effective therapy in conjunction with prompt catheter removal are the keys to successful management of Bacillus bacteremia.
Keywords: Bacillus; neonate; sepsis; bloodstream infections